If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 78 = 6x + 6 Reorder the terms: 78 = 6 + 6x Solving 78 = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 78 + -6x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 78 + -6x = 6 + 0 78 + -6x = 6 Add '-78' to each side of the equation. 78 + -78 + -6x = 6 + -78 Combine like terms: 78 + -78 = 0 0 + -6x = 6 + -78 -6x = 6 + -78 Combine like terms: 6 + -78 = -72 -6x = -72 Divide each side by '-6'. x = 12 Simplifying x = 12
| x+11.5=20.5 | | -16=.8a | | 3/4÷3/2 | | 3(k+1)+2=17 | | 7/9x=6/2/9 | | 8x-2=-58+x | | -2=x-(-1) | | 1=b-8/2 | | 1x+1=2x+1 | | g-20/-2=0 | | 12xy^2-14x^3y^3-5y/2y^2 | | 3X-2=1/ | | 5243=49(p+40) | | -16=2(h+-13) | | 6-(2+3z)=-24 | | 10=3(s+1)+1 | | 5/13=t-16/3 | | -4=1-q | | 64n^2-9=0 | | 4(k+3)-(3k-5)=4 | | N/8=17 | | 1/2x-1=1/12x | | 7(x+8)=8+7x+14 | | 5x-3y=50 | | -2(-d-a)=3d+14 | | 9x-4x+120=9x+56 | | 742.61=2*3.14*256+2*3.14*r*16 | | 10x-17=10x-17 | | =-4-(6(2x-4)-6x) | | 0.25x=1228 | | 3x+2=12x-25 | | 1/3v-8/5=-3/2 |